Exclusion of solar UV radiation increases the yield of curcuminoid in Curcuma longa L. - Ferreira, Maria Izabela [UNESP]; Uliana, Maira Rodrigues; Costa, Sergio Marques [UNESP]; Magro, Massimiliano; Vianello, Fabio; Ming, Lin Chau [UNESP]; Pereira Lima, Giuseppina Pace [UNESP] (Elsevier B.V., 2016)
In this study, we grew Curcuma longa in field conditions under a range of shade levels and the exclusion of solar UV wavelengths to determine the effects of solar UV exclusion during cultivation on the physiology and production of curcuminoids. To broaden the biochemical characterization, the activities of L-phenylalanine ammonia-lyase (PAL) and peroxidase (POD), as well as total phenol content (TP) and polyamines (PAs), were considered. We discovered that the curcumin and DMC content remain unaltered, however BDMC was higher in the turmeric under 50% shading, comparing with UV exclusion. Although the total curcuminoid cohtent remain unaltered, UV exclusion led to higher CO2 net assimilation, biomass production and consequently, a notable 21% increase of total curcuminoid yield, compared with the best result obtained by standard shading; thus UV exclusion improved total curcuminoid yield and this result may be important to the development of C. longa with high rhizome yield and with high curcuminoid content. This finding underlines the importance of selective wavelengths in C. longa cultivation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Turmeric; Photosynthesis; Biomass; Polyamine; POD; PAL